Marriage Treasure Ownership in Arabic and Nusantara Fiqh Perspectives - Khoirin, Nur (ADDIN, 2018)
One of the problems that often arise after the divorce is the ownership of assets acquired during marriage, whether it belongs to the husband, wife, or both of them. According to the Compilation of Islamic Law or the fiqh of the results of ijtihad fuqaha Nusantara, the assets obtained in marriage, except those obtained through inheritance or grants from parents/family, are joint property of husband and wife (gono gini). One party may not use it except getting agreement from the other parties. And if marriage breaks, either because of divorce or death, then it must be divided into two. In the books of Arabic Fiqh, there is no joint property because marriage does not cause a mixture of wealth. Nonetheless, in the books of fiqh provides the possession of wife's assets, such as dowry, livelihood, mut'ah, iwadl and tirkah. If the provision of fiqh is carried out consistently, then when a divorce occurs, the husband must leave the house, because all the property has become the property of his wife through a way of life. But this is certainly not fair. Therefore the determination of the existence of joint property in marriage is a moderate opinion and a benefit.